2023
DOI: 10.1371/journal.pone.0288684
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of molecular dynamics results of three-dimensional RNA aptamer structure prediction

Abstract: Aptamers are single-stranded DNA or RNA that bind to specific targets such as proteins, thus having similar characteristics to antibodies. It can be synthesized at a lower cost, with no batch-to-batch variations, and is easier to modify chemically than antibodies, thus potentially being used as therapeutic and biosensing agents. The current method for RNA aptamer identification in vitro uses the SELEX method, which is considered inefficient due to its complex process. Computational models of aptamers have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Taking into account the wealth of information provided by computational studies performed in this field [147,148], this gap of information could be filled by systematically investigating the intrinsic structural/dynamics in the unbound state of the aptamers whose structure complexed with proteins is available. Studies of this type conducted on the aptamers targeting the ribosomal S8 protein [143] or NF-κB [144] demonstrated that protein-aptamer recognition may rely on different mechanisms, i.e., induced fit or population selection.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the wealth of information provided by computational studies performed in this field [147,148], this gap of information could be filled by systematically investigating the intrinsic structural/dynamics in the unbound state of the aptamers whose structure complexed with proteins is available. Studies of this type conducted on the aptamers targeting the ribosomal S8 protein [143] or NF-κB [144] demonstrated that protein-aptamer recognition may rely on different mechanisms, i.e., induced fit or population selection.…”
Section: Discussionmentioning
confidence: 99%
“…Both NVT and NPT equilibrations were performed for 1ns each followed by a production run of 100ns for all complexes [ [74] , [75] , [76] , [77] ]. The simulations were performed on the set parameters of 298K temperature and 1.02 atm pressure using CHARMM36 force fields [ [78] , [79] , [80] , [81] ]. Despite its limitations, CHARMM36 remains one of the most reliable force fields available for RNA simulations [ [78] , [79] , [80] , [81] ], making it a suitable choice for our study.…”
Section: Methodsmentioning
confidence: 99%
“…The simulations were performed on the set parameters of 298K temperature and 1.02 atm pressure using CHARMM36 force fields [ [78] , [79] , [80] , [81] ]. Despite its limitations, CHARMM36 remains one of the most reliable force fields available for RNA simulations [ [78] , [79] , [80] , [81] ], making it a suitable choice for our study. Analysis of all trajectories including RMSD, Rg and Bonds were evaluated on VMD 1.9.3 software [ 82 ].…”
Section: Methodsmentioning
confidence: 99%